Saudi Arabia’s Reach in Yemen: Fighting for Regional Dominance - Dorsey, James Michael (2015)
The wars in Yemen and Syria represent a battle for regional dominance between Saudi Arabia and Iran. Military victory in south Yemen may, however, prove difficult to translate into sustainable political achievement.